Kajian perubahan warna gonad kerang mutiara hitam Pinctada margaritifera berdasarkan ukuran cangkang di perairan Teluk Talengen, Kepulauan Sangihe - Bawekes, Frisley Rici; Kalesaran, Ockstan J.; Lumenta, Cyska; Mingkid, Winda M.; Kusen, Diane J.; Sambali, Hariyani (Universitas Sam Ratulangi, 2024)
The black pearl oyster Pinctada margaritifera (Linnaeus, 1758) or black lip pearl oyster is a marine bivalve with important economic value. P. margaritifera is a protandrous hermaphroditic species. Externally it is difficult to differentiate between male and female gonads. This research aimed to determine differences in gonad color and determine the sex of P. margaritifera based on shell size. The test animals used in this research were black pearl mussels P. margaritifera totaling 33 samples taken from Talengen Bay, Sangihe Islands Regency, North Sulawesi. The results of morphometric measurements showed the average shell length was 103.16 mm, where the maximum shell length was 131.61 mm and the minimum was 81.29 mm. The average shell width was 105.65 (max 141.17 mm-min 83.21mm), the average shell thickness was 32.46 mm (max 44.36, min 20.11mm). The gonads were white and slightly yellow in 24 males and yellow in 9 females. P. margaritifera with a shell length of 90-130 mm was found to be female, and most were 110-120 mm in size. Meanwhile, shell lengths <80 mm and 110-130 mm male pearl oysters were still found. Keywords: marine bivalve, growth rate, morphometric, shell length